Gut Microbiota Regulates Mincle Mediated Activation of Lung Dendritic Cells to Protect Against Mycobacterium tuberculosis - Negi, Shikha; Pahari, Susanta; Bashir, Hilal; Agrewala, Javed N. (Frontiers in Immunology, 2019)
Gut microbial components serve as ligand for various pathogen recognition receptors (PRRs) present on immune cells and thereby regulates host immunity. Dendritic cells (DCs) are highly specialized innate cells involved in immune response to Mycobacterium tuberculosis (Mtb) infection. The gut-lung axis is a potential therapeutic target in tuberculosis; however, understanding of the innate immune mechanism underlying the interaction of gut microbiota and lung still remains obscure. We investigated if antibiotics (Abx) induced gut dysbiosis is able to affect the activation of innate receptor, macrophage inducible C-type lectin (mincle) in lungs during Mtb infection. We found that dysbiosis reduced the lung mincle expression with a concomitant increase in Mtb survival. Further, Abx diminished the effector and memory T cell population, while elevating frequency of regulatory T cells (Tregs) in the lungs. Here, we show that dysbiotic mice exhibited low mincle expression on lung DCs. These DCs with impaired phenotype and functions had reduced ability to activate naïve CD4 T cells, and thus unable to restrict Mtb survival. In vivo administration of trehalose-6,6-dibehenate (TDB: mincle ligand) efficiently rescued this immune defect by enhancing lung DCs function and subsequent T cell response. Further, gut microbial profiling revealed augmentation of Lactobacillus upon mincle stimulation in microbiota depleted animals. Accordingly, supplementation with Lactobacillus restored mincle expression on lung DCs along with anti-Mtb response. Our data demonstrate that gut microbiota is crucial to maintain DC-dependent lung immune response against Mtb, mediated by mincle. Abx interrupt this process to induce impaired T cell-response and increased susceptibility to Mtb.